Analisis Pengendalian Kualitas Pintu Wing King Door Menggunakan Metode Statistical Quality Control - Six Sigma Pada PT Wadja Karya Dunia Pati - Amanda Ardita Amelia; Dana Prianjani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the quality control of Wing King Door products at PT Wadja Karya Dunia Pati using Statistical Quality Control (SQC) and Six Sigma methods. Data was collected during January 2024 with a total production of 10,880 units, and 1,162 defective products were identified. The main types of defects included broken rivets, scratches, dents, and gaps, with broken rivets being the dominant defect. Analysis was conducted using SQC tools such as check sheets, histograms, p-charts, Pareto diagrams, and fishbone diagrams. The results indicate that the production process is not yet fully stable, as there is data outside the control limits. A DPMO value of 208,571.4 with a sigma level of 2.7 indicates that process quality remains low. The causes of defects include human factors, machinery, methods, environment, and materials. Improvement proposals were made using the 5W+1H approach, including operator training, machine maintenance, SOP evaluation, workplace organization, and material control. The implementation of these improvements is expected to reduce defect rates and continuously improve product quality.